Leadership style and employees’ performance in Pakistan: The mediating role of organisational commitment - Abbasi, Muhammad Nauman; Ali, Asif; Khalid, Muhammad Ahsan (UUM Press, 2019)
The paper investigates the critical role of organisational commitment between leadership style and employees performance. Generally, the relationship between leadership style and the organisational performance has been discussed widely but ignoring the employees performance. It has been accepted that the organisational commitment leads to higher employee performance but the existing literature has not focused much on this view. A conceptual model has been developed which links the constructs together. The model reveals the missing link of organisational commitment between leadership style and employees performance. The sample of 242 was collected from the managers and employees of manufacturing and service organisations. The finding confirmed that organisational commitment acted as a mediator between the leadership style and employees performance.